The numerical electromagnetic analysis of complex structures : with specific reference to HF radiation from the aerospatiale SA330 Puma helicopter - Le Roux, J. J.(Jacques Johannes) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1989.